Negative association between MR‐spectroscopic glutamate markers and gray matter volume after alcohol withdrawal in the hippocampus: a translational study in humans and rats - Frischknecht, Ulrich; Hermann, Derik; Spanagel, Rainer; Kiefer, Falk; Mann, Karl; Sommer, Wolfgang H.; Ende, Gabriele (Alcoholism, 2017)
Background: Both chronic alcohol consumption and alcohol withdrawal lead to neural tissue damage which partly recovers during abstinence. This study investigated withdrawal‐associated changes in glutamatergic compounds, markers of neuronal integrity, and gray matter volumes during acute alcohol withdrawal in the hippocampus, a key region in development and maintenance of alcohol dependence in humans and rats. Methods: Alcohol‐dependent patients (N = 39) underwent magnetic resonance imaging (MRI) and MR spectroscopy (MRS) measurements within 24 hours after the last drink and after 2 weeks of abstinence. MRI and MRS data of healthy controls (N = 34) were acquired once. Our thorough quality criteria resulted in N = 15 available spectra from the first and of N = 21 from the second measurement in patients, and of N = 19 from healthy controls. In a translational approach, chronic intermittent ethanol‐exposed rats and respective controls (8/group) underwent 5 MRS measurements covering baseline, intoxication, 12 and 60 hours of withdrawal, and 3 weeks of abstinence. Results: In both species, higher levels of markers of glutamatergic metabolism were associated with lower gray matter volumes in the hippocampus in early abstinence. Trends of reduced N‐acetylaspartate levels during intoxication persisted in patients with severe alcohol withdrawal symptoms over 2 weeks of abstinence. We observed a higher ratio of glutamate to glutamine during alcohol withdrawal in our animal model. Conclusions: Due to limited statistical power, we regard the results as preliminary and discuss them in the framework of the hypothesis of withdrawal‐induced hyperglutamatergic neurotoxicity, alcohol‐induced neural changes, and training‐associated effects of abstinence on hippocampal tissue integrity.
Gesehen am 05.04.2018